ENVIRONMENTAL MEDIA ACTIVIST JOURNALISM: contributions from an analysis of journalistic coverage from Amazonia Real - Franco de Souza, Amanda; Miguel, Katarini (Brazilian journalism research, 2023)
ABSTRACT – Our research aims to understand and problematize the proximity between environmental journalism and media activist practice based on the journalistic coverage analysis (Silva & Maia, 2011) of the Amazônia Real portal, adapted to our empirical efforts in a media activist environmental journalism protocol. Within the limits of this article, we presented an analytical exercise with two reports that showed the assumptions of environmental journalism: emphasis on contextualization, plurality of voices, assimilation of environmental knowledge (Loose & Girardi, 2017) and the discursive tactics of media activism, with engagement and opinion revealed in what we call the manifesto report. However, we noticed the underutilization of technological resources and the presentation of events in a conventional narrative structure, which strains the praxis of media activist environmental journalism. RESUMO – Nossa pesquisa busca entender e problematizar as proximidades entre o jornalismo ambiental e a prática midiativista a partir da análise de cobertura jornalística (Silva & Maia, 2011) do portal Amazônia Real, adaptada aos nossos esforços empíricos em um protocolo de jornalismo ambiental midiativista. Apresentamos, nos limites deste artigo, um exercício analítico com duas reportagens que evidenciaram os pressupostos do jornalismo ambiental: ênfase na contextualização, pluralidade de vozes, assimilação do saber ambiental (Loose & Girardi, 2017) e as táticas discursivas do midiativismo, com o engajamento e a opinião revelados no horizonte do que denominamos de reportagem-manifesto. Contudo, notamos o subaproveitamento dos recursos tecnológicos e apresentação dos acontecimentos em uma estrutura narrativa convencional, que tensionam a práxis do jornalismo ambiental midiativista. RESUMEN – Nuestra investigación busca comprender y problematizar la proximidad entre el periodismo ambiental y la práctica activista de los medios, a partir del análisis de cobertura periodística (Silva & Maia, 2011) del portal Amazônia Real, adaptado para el estudio empírico mediante un protocolo de aproximación al periodismo ambiental activista. Presentamos, dentro de los límites de este artículo, un ejercicio analítico con dos reportajes en los que aparecen los supuestos del periodismo ambiental: énfasis en la contextualización, pluralidad de voces, asimilación del conocimiento ambiental (Loose & Girardi, 2017) y las tácticas discursivas del activismo mediático, con compromiso y opinión revelados en lo que llamamos un reportaje manifiesto. Sin embargo, observamos la subutilización de los recursos tecnológicos y la presentación de los acontecimientos en una estructura narrativa convencional, lo que genera tensiones en la praxis del periodismo medioambiental activista en los medios.